Analgesic and cytotoxic activity of Acorus calamus L., Kigelia pinnata L., Mangifera indica L. and Tabernaemontana divaricata L. - Mohammad Ahad Ali Khan; Mohammad Torequl Islam (Wolters Kluwer Medknow Publications, 2012)
Objectives: The aim of the study was to evaluate analgesic and cytotoxic activity of Acorus calamus L., Kigelia pinnata L., Mangifera indica L., Tabernaemontana divaricata L. extracts by using acetic acid-induced writhing method in mice and brine shrimp lethality assay. Materials and Methods: The ethanolic extracts of the plants were obtained by simple maceration method and were subjected to standardization by using pharmacognostical and phytochemical screening methods, which were followed by acetic acid writhing and brine shrimp lethality test methods. Dose selection was made on the basis of acute oral toxicity study (10-1000 mg/kg body weight). Results and Conclusion: In analgesic test, M. indica L. extract produced 28.16% and 22.02% writhing protection at the doses of 250 and 500 mg/kg body weight in mice, respectively. While the T. divaricata L. extract produced 22.02% and 33.93%, K. pinnata L. extract produced 11.55% and 47.29% and A. calamus L. extract produced 15.16% and 54.51% of writhing protection at the same doses. The percent mortality (mean ± SD) was found to be 58.7 ± 25.22, 56.25 ± 22.88, 52.50 ± 24.37, and 61.25 ± 26.66 with M. indica L., T. divaricata L., K. pinnata L., and A. calamus L., respectively. And the LC 50 and LC 90 values were found to be 100 and 300 μg/mL for M. indica L. and that were (200 and 350 μg/mL), (100 and 350 μg/mL) and (50 and 300 μg/mL) for T. divaricata L., K. pinnata L., and A. calamus L., respectively. Thus it can be concluded that bark of M. indica L., leaves of T. divaricata L., bark of K. pinnata L., and roots of A. calamus L. have significant analgesic and cytotoxic activity and can be preferred in the treatment of pain and tumor.